Optimization of Social Report as a Consideration of Diversion in The Child Criminal System - Rommy Yusuf Hiola; Aliyas Aliyas; Suardi Rais (Jurnal Hukum Volkgeist, 2021)
There is one factor that becomes an obstacle if the child has received the coaching process at the Child Special Guidance Institute (hereinafter referred to as LPKA), namely the existence of "stigmatization" attached to the child so that it does not make it easier for children to socialize. The "Labeling" theory shows that labeling or in other words this stigmatization can damage the future of children where the future is still long. Therefore, the application of imprisonment for children must be an "ultimum remedium" or "the last resort", which means that imprisonment must be the last resort. This is where the diversion function lies as the concept of solving children's problems without going through a trial so that children are not burdened by negative stigma that will be attached to them, but in practice the diversion process often experiences obstacles, one of which is the lack of understanding of law enforcement towards the situation and condition of children, this is because not optimal community research or social reports on children in conflict with the law. The specific purpose of this research is to identify and analyze the factors that cause the non-optimal implementation of social reports on children's cases and to find out the efforts made in maximizing social reporting in an effort to implement diversion in children's cases. The method used in this research is empirical research, namely research with field data as the main data source, such as the results of interviews and observations